PATTERNS OF PRINCIPAL LEADERSHIP IN IMPROVING TEACHER PERFORMANCE AT ALIF INAYAH PRIVATE ELEMENTARY SCHOOL IN MEDAN - Maulia Maulia; Dina Puspita; Rabbul Khairi; Mhd. Isman; Lilik Hidayat (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this study was to determine the leadership pattern of the principal in improving teacher performance at Alif Inayah Private Elementary School in Medan. The research was carried out at Alif Inayah Private Elementary School in Medan using data collection techniques of observation, interviews, documentation and questionnaires. The research results show Leadership principal of Alif Inayah Private Elementary School in accelerating the tasks of teachers by being innovative and creative from old situations in new ways, by involving all components in solving and making decisions. Paying special attention to the needs of the teachers at Private Alif Inayah Elementary School in Medan is proven by the head of the school who has been a good listener to teachers who face problems and need problem solving and attention. Head ability inner school provide motivation teachers At Alif Inayah Medan Private Elementary School, it is reflected in the discipline of time and neatness in dress which is an example for teachers to carry out their duties optimally. The teachers admired the principal and tried to set an example by doing the same as the principal did, namely prioritizing organizational interests over personal interests. The principal at Alif Inayah Medan Private Elementary School also always involves the school community in compiling school activity programs so that subordinates will really feel part of the organization and are responsible for the tasks given, and work together with teachers in improving professional competence. Planning to improve the performance of the Alif Inayah Medan Private Elementary School teachers was carried out by preparing a plan to improve teacher quality by basing it on the vision, mission and objectives of the school that had been planned. Planning is carried out by involving all the school's academic community, including involving teachers in determining future programs or plans. The planning carried out by the school principal is also based on a needs analysis and job analysis. Meanwhile, the efforts of the school principal in improving the performance of the Alif Inayah Medan Private Elementary School teachers are carried out by involving teachers in scientific forums (seminars, training, workshops, workshops and courses), further studies, revitalization of the KKG, welfare allowances,